Financial Performance - Ahtikoski, Anssi; Gong, Peichen; Rorstad, Per Kr; Viitala, Esa-Jussi; Repo, Jaakko (Springer Nature Switzerland, 2025)
Financial comparisons between rotation forestry (RF) and continuous cover forestry (CCF) are based on simulations in which the growth and yield of trees is estimated using a growth simulator. These often include an optimisation tool to present the maximum value of the objective function (usually the present value of net income). Studies have shown that the profitability of CCF depends on the initial state of a stand, especially the diameter distribution of the trees. The effect of interest discount rate also depends on the initial state. As a rule, it is safe to say that the more the forest structure resembles the target diameter distribution of the trees in CCF (i.e., a forest with heterogeneous structures), the more profitable it is to shift from RF to CCF. The more heterogeneous the tree structure on mineral soil, the higher the applied interest rate, the higher the forest establishment costs (soil preparation and cultivation), and the poorer the growth conditions (site type and temperature sum), the more profitable CCF is. Few studies have been found that focus on peatland forests. Future financial studies should also consider risks associated with wind, harvesting, and insect and fungus damage as well as carbon payments and nontimber benefits.
Keywords: stand-level optimisation; rotation forestry; continuous cover forestry; profitablity; economic-ecological model